Smart Homes and Ambient Assisted Living Applications: From Data to KnowledgeEmpowering or Overwhelming Older Adults? - Demiris, G.; Thompson, H. (Yearbook of Medical Informatics, 2011)
As health care systems face limited resources and workforce shortages to address the complex needs of older adult populations, innovative approaches utilizing information technology can support aging. Smart Home and Ambient Assisted Living (SHAAL) systems utilize advanced and ubiquitous technologies including sensors and other devices that are integrated in the residential infrastructure or wearable, to capture data describing activities of daily living and health related events. This paper highlights how data from SHAAL systems can lead to information and knowledge that ultimately improves clinical outcomes and quality of life for older adults as well as quality of health care services.We conducted are view of personal health record applications specifically for older adults and approaches to using information to improve elder care. We present a framework that show cases how data captured from SHAAL systems can be processed to provide meaningful information that becomes part of a personal health record.Synthesis and visualization of information resulting from SHAAL systems can lead to knowledge and support education, delivery of tailored interventions and if needed, transitions in care. Such actions can involve multiple stakeholders as part of shared decision making.SHAAL systems have the potential to support aging and improve quality of life and decision making for older adults and their families. The framework presented in this paper demonstrates how emphasis needs to be placed into extracting meaningful information from new innovative systems that will support decision making. The challenge for informatics designers and researchers is to facilitate an evolution of SHAAL systems expanding beyond demonstration projects to actual interventions that will improve health care for older adults.
Keywords: Smart homes; ambient assisted living; shared decision making; personal health record; gerontology; geriatrics